P248 Lifestyle changes after Inflamatory Bowel Disease diagnosis. (21st January 2022) - Belén Galipienso, O; Cameo, J; Bernabeu, P; Mira, C; García, M D M; Pomares, C; Muñoz, D; Canales, N; Gutierrez, A; Zapater, P; van-der Hofstadt, C; Jover, R; et al.
Abstract: Background: Some lifestyle factors seem to modify the course and clinical outcomes in patients with Inflammatory Bowel Disease (IBD). A higher level of exercise has been associated with lower risk of relapse among patients in remission whereas obesity increases the risk of treatment failure. Moreover, sleep disturbances and stress have been associated with a higher risk of flare up. The relationship between various lifestyle factors and IBD seems to be bi-directional. In clinical practice, we observe lifestyle changes in patients with IBD unknowing exactly their incidence. The aim of this study is to assess lifestyle changes after IBD diagnosis. Methods: Prospective and multicenter observational study in patients with new diagnosis of IBD. Semi-structured interviews were conducted evaluating lifestyle changes (diet, physical activity, rest, relaxation techniques, and leisure activities) in the first 6 months after IBD diagnosis. Results: 154 patients were included 79 (51.3%) Crohn's disease (CD), 75 (48.7%) Ulcerative Colitis (UC). 68 (44.2%) women, 86 (55.8%) men. Mean age 42.5 years (±16.1). BMI 24.9 ± 5. 67 (43.5%) were never-smokers, 26 (16.9%) smokers, 61 (39.6%) ex-smokers. Lifestyle changes consisted in dietary modifications in 94 (61%) patients, increased physical activity in 43 (27.9%) patients, increased time for resting in 32 (20.8%) patients, the use of relaxation techniques in 11 (7.1%) patients and increased leisure activities in 27 (17.5%) patients. There were no differences in lifestyle changes between CD patients and UC patients except for the diet, which was more often modified by CD patients than UC patients [58 (73.4%) vs. 36 (48%) p=0.001, OR 95% 2.9 (1.5–5.8)]. Regarding differences between both sexes, men more frequently increased exercise than women [30 (34.9%) vs. 13 (19.1%) p=0.03 OR 95% 2.2 (1.07-4-7)]. There were no differences in rest, relaxation, leisure activities and dietary changes between men and women. Age was not associated with changes in lifestyle, except for leisure activities, which were more often increased in patients under 40 years of age than patients over 40 years of age [17 (23.9%) vs 10 (12%) p=0.053, OR 95% 2.2 (0.97–5.4)]. Conclusion: Lifestyle changes in IBD patients appear soon, and diet is the most frequently modified habit.